Network analysis in depressed adolescents with suicidal ideation: the role of depression, anxiety, and childhood abuse - Huang, Ziyang; A, Liya; Yan, Kewen; Ran, Hailiang; Che, Yusan; Yang, Runxu; Jiang, Linling; Xiao, Rui; Zeng, Rushuang; Li, Tong; Xie, Yiling; Xiao, Yuanyuan; et al. (Frontiers in Psychiatry, 2025)
IntroductionAdolescent depression is a global public health issue strongly associated with suicidal ideation and childhood abuse. Although family systems and ecological theories highlight the multilevel influences of family environment on mental health, most studies focus on overall symptom scores rather than examining how specific forms of abuse relate to distinct symptoms. Employing symptom network analysis, this study investigates the interactions among depressive symptoms, anxiety, and childhood abuse in adolescents diagnosed with major depressive disorder (MDD) and suicidal ideation.MethodsWe analyzed data from 733 Chinese adolescents diagnosed with MDD (mean age = 14.81 years). Symptom networks were constructed via LASSO-regularized models using the Patient Health Questionnaire-9 (PHQ-9), Generalized Anxiety Disorder-7 (GAD-7), and the Childhood Trauma Questionnaire-Short Form (CTQ-SF). Centrality (strength and bridge strength) and stability analysis identified core symptoms and bridging pathways.ResultsDepressive and anxiety symptoms showed strong comorbidity, with “Uncontrollable worry” (GAD2) and “Fatigue” (PHQ4) as central nodes. Key bridge symptoms included “Motor” (PHQ8), “Death” (PHQ9), “Restless” (GAD5), and “Emotional abuse” (EA). Childhood abuse exhibited intra-group correlations (emotional-physical abuse), and emotional abuse was directly linked to death-related thoughts. The network demonstrated strong stability.ConclusionsEmotional abuse and bridge symptoms (e.g., fatigue and uncontrolled worry) are critical intervention targets for suicide−prevention interventions. A multimodal approach integrating cognitive-behavioral therapy for core symptom management, family-based interventions to address attachment disruptions, and policy initiatives to reduce childhood abuse is recommended.